Criminal Procedure And The Banking And Financial Institutions Act 1989 - Majid, Mimi Kamariah (Journal of Malaysian and Comparative Law, 2019)
The Banking and Financial Institutions Act 1989 (BANFIA) came into force in two stages. On 1st October 1989 all provisions of the Act, except those in respect of scheduled institutions, came into force. All provisions of the Act in respect of scheduled institutions came into force on 1st January 1990.